Sanguinaria mexicana (Polygonum aviculare L.). Aplicaciones y beneficios - González Begné, Mireya; Quiroz, Verónica; Reyes, Elvia; Banderas Tarabay, José Antonio; Yslas, Nicandro (CIENCIA ergo-sum, 2017)
-